KINERJA KEUANGAN DAN UMUR PERUSAHAAN SEBAGAI FAKTOR PENENTU TINGKAT UNDERPRICING PERUSAHAAN NON KEUANGAN YANG MELAKUKAN INITIAL PUBLIC OFFERING - Muspa Muspa (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to analyze the Influence of Financial Performance and the age of the company against the level of underpricing in non-financial companies that conduct Initial Public Offering. The samples used in this study amounted to 44 non-financial companies experiencing underpricing. The method of analysis used in this study is multiple regression analysis with the help of SPSS version 20.0. The observation period is 3 years from 2012 to 2014. The results of this study indicate that the Return on Equity positive and not significant, Debt to Equity Ratio and age of the company have a negative and not significant. While simultaneously, the variable Return On Equity, Debt to Equity Ratio, and age of the company together have no significant effect . The influence of Return On Equity, Debt to Equity Ratio and firm age to the underpricing variable is 5.80% and the rest is influenced by other factors not studied in this research as 94,20%.